Coronavirus disease (COVID-19): new challenges for dental practice (literature review) - Potokiy Наталія Йосипівна; Brych Валерія Володимирівна; Potapchuk Анатолій Мефодійович; Kostenko Євген Якович; Almashi Василь Миколайович; Tsutskov Олександр Олександрович; Onipko Євген Леонідович (Actual Dentistry, 2022)
Resume. An analysis of current regulations in Ukraine on the provision of dental care during quarantine in connection with the spread of coronavirus disease (COVID-19), scientific publications of foreign and domestic authors on the peculiarities of its spread and course. literature research shows that the emergence of new variants of SARS-CoV-2, which show increased transmissibility (in particular, the variant of concern to delta), forces us to constantly monitor developments in the world of this virus, update knowledge about the effectiveness of those or other anti-epidemic measures, to assess risks and implement appropriate measures to reduce them, to learn from the implementation of preventive measures in other countries and to promote active vaccination of dental workers from COVID-19 as one of the most powerful measures to combat the epidemic.